Spatio-temporal morphological variability of a tropical barrier island derived from the Landsat collection - Carvalho, Breylla Campos; Gomes, Carolina Lyra da Silva; Guerra, Josefa Varela (Frontiers in Remote Sensing, 2023)
Barrier islands are low-lying elongated, narrow sandy deposits, usually parallel to the coastline, separated from the continent by a lagoon. Due to their low elevation above sea level, barrier islands are environments susceptible to drastic morphological changes depending on the meteo-oceanographic conditions to which they are subjected. This work presents the morphological changes between 1985 and 2021 in "Restinga da Marambaia" – a 40 km long barrier island on Brazil’s Southeastern coast. One hundred thirty-four scenes from the Landsat collection were processed, enabling the quantification of the barrier island area. Additionally, the rates of change in the position of the shorelines facing the Atlantic Ocean, Sepetiba Bay, and Marambaia Bay were computed. The barrier island's total area and the central sector's width present significant seasonal variability, which is maximum during the austral fall and winter seasons. On the shores facing the Atlantic Ocean and Sepetiba Bay, it is noted that the central and far eastern sectors show an erosional trend. In contrast, the coastline is more stable on the shore facing Marambaia Bay. The seasonal variations of the barrier island area occur during a period of low rainfall and more energetic waves associated with local winds, which produce coastal currents, transporting the available sediments.